LINGUISTIC PREJUDICE IN TEACHING PRACTICE - Martins, Rosemari Lorenz; de Moura Pinto, Cíntia; Carlesso, Rachel; Maggioni Spindler, Alex Sandro; Bueno dos Santos, Jéssica Luana; Möller, Iago Ramon (Revista Conhecimento Online: Diversidade e Inclusão Social, 2018)
This article deals with the investigation of the presence of linguistic prejudice in teaching practice, in which, supposedly, high school teachers would be presuming students' performance from the use or lack of use of the standard language in speech within the school environment. The research and the production of this work was based on Marcos Bagno’s work, a relevant name on the debate on linguistic prejudice, besides other works of sociolinguists and articles on the problem of linguistic prejudice in the classroom, from what it was made a methodology that consists of the application of a questionnaire interview. The analysis of results, opened to the several possibilities of reading produced from the ambiguity and contradiction of the results, made it possible to find positive and negative points as well as new possibilities of research around the same subject. It was concluded, however, that the tendency in school environment is marginalizing the use of the language that does not meet educational standard language and pointing it as the ideal model to be reached, what reinforces the central hypothesis of this work. Keywords: Sociolinguistics. Linguistic variation. Linguistic prejudice. Adequacy. RESUMO O presente artigo debruçou-se sobre a investigação da presença do preconceito linguístico na prática docente, em que, hipoteticamente, professores do Ensino Médio pressupõem o desempenho dos estudantes a partir do uso ou não do uso da língua padrão na fala no ambiente escolar. A partir de uma reflexão sobre a obra de Marcos Bagno, nome relevante no debate sobre preconceito linguístico, além de produções de sociolinguistas e artigos sobre o preconceito linguístico na sala de aula, executou-se uma metodologia calcada, essencialmente, na aplicação de uma entrevista guiada por questionário. A análise de resultados, na medida em que se abriu para as várias possibilidades de leitura produzidas da ambiguidade e da contradição dos resultados, foi capaz de encontrar pontos positivos, pontos negativos e novas possibilidades de pesquisa no mesmo tema. Concluiu-se, porém, que a tendência no ambiente escolar é de marginalização da língua não culta utilizada pelos alunos e da visão que a língua padrão é o modelo ideal que se pretende alcançar, o que reforça, portanto, a hipótese central deste estudo. Palavras-chave: Sociolinguística. Variação linguística. Preconceito linguístico. Adequação.